2011
DOI: 10.1016/j.cub.2011.03.069
|View full text |Cite
|
Sign up to set email alerts
|

A Pair of Inhibitory Neurons Are Required to Sustain Labile Memory in the Drosophila Mushroom Body

Abstract: Summary Labile memory is thought to be held in the brain as persistent neural network activity [1–4]. However, it is not known how biologically relevant memory circuits are organized and operate. Labile and persistent appetitive memory in Drosophila requires output after training from the α′β′ subset of mushroom body (MB) neurons and from a pair of modulatory Dorsal Paired Medial (DPM) neurons [5–9]. DPM neurons innervate the entire MB lobe region and appear to be pre- and post-synaptic to the MB [7, 8], consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 42 publications
8
141
0
Order By: Relevance
“…Blocking the synaptic output from g lobe or a/b lobe neurons impairs the retrieval of aversive 3-h memory Aversive and appetitive 3-h memories formed after one-session training are typical memory phases (intermediate-term memory) for studying different processes of olfactory memory processing, including memory acquisition, consolidation, and retrieval (McGuire et al 2001;Keene et al 2006;Krashes et al 2007;Pitman et al 2011;Berry et al 2012). shibire ts1 is a dominant temperature-sensitive allele of dynamin (Kim and Wu 1990;Kitamoto 2001;Kasuya et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Blocking the synaptic output from g lobe or a/b lobe neurons impairs the retrieval of aversive 3-h memory Aversive and appetitive 3-h memories formed after one-session training are typical memory phases (intermediate-term memory) for studying different processes of olfactory memory processing, including memory acquisition, consolidation, and retrieval (McGuire et al 2001;Keene et al 2006;Krashes et al 2007;Pitman et al 2011;Berry et al 2012). shibire ts1 is a dominant temperature-sensitive allele of dynamin (Kim and Wu 1990;Kitamoto 2001;Kasuya et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Here, aversive and appetitive memories can be compared in a site-bysite manner (Schwaerzel et al, 2003). The quality of the behavioral reinforcer used during the training procedure, i.e., either sugar reward for appetitive learning or electric shock punishment for aversive learning, influences the neuronal circuits (Krashes et al, 2007(Krashes et al, , 2009Pitman et al, 2011) required to establish an appropriate memory at the level of the Drosophila MBs (Schwaerzel et al, 2003;Thum et al, 2007). When assayed for immediate aversive or appetitive memory performance, rg 1 and rg ␥5 animals show a significant reduction compared with wild-type Canton-S controls.…”
Section: Resultsmentioning
confidence: 99%
“…Clonal analysis of the GH146-Gal4 revealed that the projection of the APL neuron formed a continuous net-like innervation throughout the compartment of the ipsilateral MB except the cell body region (Liu and Davis, 2009). They inhibit olfactory learning (Liu and Davis, 2009), but promote stabilization of labile olfactory memory traces (Pitman et al, 2011;Wu et al, 2011).…”
Section: The Apl Neurons Are Required For Visual Reversal Learningmentioning
confidence: 99%